Is the fitld Test of FUT-SAT a better experimental design to identify the specific characteristics of tactical performance according to youth male soccer players' positional roles? - Ciro-Cardona, J.; Marulanda-Tabares, J.; Moniz, F.; Valencia-Sánchez, W. (Journal of Human Kinetics, 2024)
This study aimed to compare soccer players` tactical performance according to their positional roles in the field test of FUT-SAT. The sample consisted of 54 male players from elite youth clubs (Medellín-Colombia), U16 and U17 categories. Participants trained five times per week (Tier 3). We used the System of Tactical Assessment (FUT-SAT), which evaluates tactical behaviour and performance through core tactical principles of soccer. The field test is structured in a numerical configuration of a goalkeeper + 3 players vs. 3 players + a goalkeeper played during 4 min on a playing field 36 m long by 27 m wide. All teams were structured with one player in each positional role (one defender, one midfielder, and one forward). To determine the differences between the positional roles, the following factors were analysed: the number of actions, the percentage of correct actions, the place of action related to the principles, and the Tactical Performance Index of core tactical principles. A total of 2891 tactical actions distributed in nine games were analysed. A Kruskal-Wallis test for the independent groups (defenders, midfielders, and forwards) or a one-way ANOVA was used. There was no difference in soccer players` tactical performance and behaviour between players of different positional roles in the field test of FUT-SAT. Therefore, teams need to be evaluated with the system of play with players in all field sectors in medium or large sided games. The system of play can be chosen according to the category given that competitions are held in reduced spaces and with fewer players.